Optimisation of parameters of vibration control process by applying rheological dynamic model - Didžgalvis, Rimantas; Sudintas, Antanas; Tiknevičienė, Irena (Lietuvos matematikos rinkinys, 2001)
The process of vibration control in question is investigated when the sediment is described in terms of rheologic body. The summarised dynamic and mathematical models of the vibration control are presented. In the partial case the sediment is described in terms of elastic-tough-plastic body. It is assumed that the vibration power is directed to the surface under cleaning at a certain angle therefore the process is analysed in tangent and normal directions. There is detennined optimum criteria for the vibration control process. The solution of the system is presented for the case when the angle of the influence power θ = 1. There are presented the main characteristics of the process and conclusions on it.